1994
DOI: 10.1007/bf01406498
|View full text |Cite
|
Sign up to set email alerts
|

Change in regional cerebral blood flow following glycerol administration predicts

Abstract: Cerebral haemodynamics were measured in 22 adult patients with secondary normal pressure hydrocephalus (NPH) before and after glycerol administration to determine which patients might benefit from a shunt procedure. Of these 22 patients, 14 were found to be shunt-responsive (group 1) and 8 were shunt-unresponsive (group 2). Measurement of regional cerebral blood flow (rCBF) was performed by xenon-enhanced computerized tomography (XeCT). Clinical factors such as the Evans' index and the presence or absence of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Different methods of cerebral perfusion imaging, such as xenon measurements [1,4,[11][12][13][14], 99m Tc-hexamethylpropylene amine oxime single photon emission computed tomography ( 99m Tc-HMPAO SPECT) [15], 99m Tc-ethyl cysteinate dimer ( 99m Tc-ECD) SPECT [16] and 123 Iisopropyl amphetamine ( 123 I-IAMP) SPECT [6], have shown a positive correlation between increased cerebral blood flow after CSF tap test and clinical improvement after CSF shunting procedures. However, conflicting results have been reported [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods of cerebral perfusion imaging, such as xenon measurements [1,4,[11][12][13][14], 99m Tc-hexamethylpropylene amine oxime single photon emission computed tomography ( 99m Tc-HMPAO SPECT) [15], 99m Tc-ethyl cysteinate dimer ( 99m Tc-ECD) SPECT [16] and 123 Iisopropyl amphetamine ( 123 I-IAMP) SPECT [6], have shown a positive correlation between increased cerebral blood flow after CSF tap test and clinical improvement after CSF shunting procedures. However, conflicting results have been reported [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Others believe that a fall in cerebral blood flow is a secondary phenomenon resulting from a decrease in cerebral metabolism caused by a decrease in volume of brain tissue in normal pressure hydrocephalus (19–21). Some authors have found no alterations in cerebral hemodynamics after shunt therapy (6–8, 16), whereas others found significant improvement in cerebral blood flow (9–11) and cerebrovascular reactivity (7, 10–12), and a reduction in PI (13). A remarkable observation in our study was the decrease in blood flow velocities in patients with and without clinical improvement after shunt surgery, suggestive for a possible postoperative normalization in intraparenchymal pressure and concomitant relaxation of large arteries.…”
Section: Discussionmentioning
confidence: 98%
“…A global cerebral blood flow reduction, more severe in the frontal lobes, has been observed in patients with normal pressure hydrocephalus (9, 16). This reduction in cerebral blood flow in patients with NPH is considered a result of increased intraparenchymal pressure in the brain with compression of small‐calibre vessels (10, 17, 18). Others believe that a fall in cerebral blood flow is a secondary phenomenon resulting from a decrease in cerebral metabolism caused by a decrease in volume of brain tissue in normal pressure hydrocephalus (19–21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations